Presentation Open Access The Maritime Silk Road: A Euro-Sino Economic, Political and Geo-strategic Challenge - Marsili, M. (Doctoral Seminar Carlos V European Award – Antonio Tajani: "The European Union and the Principle of Solidarity" (Carlos V European Award 2019 - Antonio Tajani), 2021)
In an era of increasing economic interdependence China is playing a growing role in the global economy, including in Europe, which presents both opportunities and challenges. This paper aims to analyze the different dimensions of an increasingly assertive Chinese presence in Europe from economics to politics and geo-strategy. The essay will address the China’s Belt and Road initiative (BRI), the ‘Made in China 2025’ plan, the China 17+1 initiative and Trade disputes between China and Europe. It will also look at questions of technology competition and critical infrastructure investment. China's leaders announced in October 2017 that they want to assume a global leadership role. The long-term strategic competition with the People’s Republic of China (PRC) is one of the major global economic, military and political challenges. Maritime policies play an important role in support of that strategy of making China a global leader. Today, Beijing is seeking to project sophisticated power globally, particularly in areas with heavy BRI activity – the plan for greater connectivity for China across both land and sea through a new Silk Road. The 21st Century Maritime Silk Road affects Europe in five main areas: maritime trade, shipbuilding, emerging growth niches in the blue economy, the global presence of the Chinese navy, and the competition for international influence. It has been calculated that the Maritime Silk Road creates more competition than cooperation opportunities in Europe-China relations. The sea lanes of communication from China to Europe through the Malacca-Suez route are among the busiest in the world – where European interests are more immediate and bigger than on the nascent "Ice Silk Road": China-Europe maritime trade is three times larger than trade by air freight and Eurasian railways, while the last alternative – the Northern Route through the Arctic Ocean, that China dubs the "Ice Silk Road" – is only just starting to develop. In January 2018, the PRC published its first Arctic strategy that promoted a "Polar Silk Road" and claimed to be a "Near-Arctic State", yet the shortest distance between China and the Arctic is 900 miles. Russia announced plans to connect the Northern Sea Route with China’s Maritime Silk Road – part of the BRI strategy – which would develop a new shipping channel from Asia to northern Europe, and the two counties are cooperating in developing hydrocarbon resources in the Arctic. Meanwhile, China is already developing shipping lanes in the Arctic Ocean. There are warnings about the Arctic Ocean to be transformed into 'a new South China Sea', militarized and with territorial claims. The Pentagon warned that China could use its civilian research presence in the Arctic to strengthen its military presence – including deployment of submarines to the region as a deterrent against nuclear attack. This paper aims also to investigate the impact of the Chinese maritime geo-strategy over the European security. Arctic security is a main security challenge – a global one, not only a regional one – not only for the Arctic countries, but for the whole international community, first of all the European. With Russia and China expanding their role in the area, and the difficulty of finding an undisputed governance on maritime routes and economic exploitation of resources, there is the risk of militarization of the Arctic. After briefly summarizing current and future challenges in the Arctic, this paper analyzes the limits due to a deficit of suitable instruments to maintain security in the region, especially in relation to the role of international intergovernmental organizations, and it suggests some remedies to overcome these deficiencies. The Arctic region has become an arena for power and for competition, and Arctic nations must adapt to this new future. Offshore resources are the subject of renewed competition: Arctic region holds the greatest concentration of the world’s undiscovered oil and gas, uranium, gold, diamonds, rare earth minerals – phosphate, bauxite, iron ore, copper, and nickel – and, last but not least, fish. Arctic resources should be included in the common domain; they should be considered common goods – international or global public goods. Nowadays, environmental and economic issues are broadly considered to be threats to security and stability. Therefore, the protection of these resources is a security issue, which involves the use of force, or military means. This is an issue that concerns the traditional domains of operations – land, sea, and air. The maritime domain – i.e. the Arctic Ocean – is predominant, due to the allocation of resources, and the operating environment. Sea routes are the ‘liquid’ highways along which goods travel across the world, and therefore play a strategic economic role – a global one.